On the 80th Anniversary of Alexander Semenovich Kovalev - Ivanov, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2025)
May 18, 2025 marks the 80th birthday of outstanding theoretical physicist, Doctor of Physical and Mathematical Sciences, Professor A. S. Kovalev. A. S. Kovalev graduated from school in 1962 and entered the Physics Department of V. N. Karazin Kharkiv National University, where he attended lectures by I. M. Lifshitz and his colleagues —M. I. Kaganov, E. A. Kaner, A. M. Kosevich, G. Y. Lyubarsky, and Y. I. Lyubich. After graduating from the university in 1967, A. S. Kovalev began working at the Kharkiv Institute of Physics and Technology in the Department of Theoretical Physics led by I. M. Lifshitz, in A. M. Kosevich’s laboratory. Here, he once again found himself in the remarkable atmosphere of the school of I. M. Lifshitz, which determined his scientific destiny and played a decisive role in his formation as a scientist.